COMPARATIVE ASPECTS OF ELECTRICAL EROSION PROCESSES (Nonconventional Technologies Review, 2023)
The paper presents some theoretical aspects regarding the dimensional processing procedures by electrical erosion. A classification of the EE processing variants and their characterization according to the considered criteria is presented. In summary, the definition of specific concepts, their scope, as well as different schemes, technological methods, as well as specific characteristic operations for the four electrical erosion processing processes are presented. The paper presents some theoretical aspects regarding the dimensional processing procedures by electrical erosion. A classification of the EE processing variants and their characterization according to the considered criteria is presented. In summary, the definition of specific concepts, their scope, as well as different schemes, technological methods, as well as specific characteristic operations for the four electrical erosion processing processes are presented.
Keywords: erosion; electrical erosion; object subject to processing (OP); tool electrode (ES); transfer object (OT); electrical contact; processing method; principle diagram; forms of electrical erosion; electrical discharges; contact breakage; erosive agent; processing operations; differentiation criteria; impulse; filiform electrode (EF); generation of surfaces